What Is Assumed about a Catholic Student’s Ecclesial Agency, and Why It Matters to Catholic Schooling - McDonough, Graham P. (Catholic Education: A Journal of Inquiry and Practice, 2011)
This paper shows that a lack of explicit and clearly stated intentions regarding the development of Catholic students’ ecclesial agency through their schooling leads to potential problems as they experience and imagine themselves as lay persons in the Church. While the question of “ecclesial agency” applies throughout all Catholic schooling and the whole Church, in practice the usual flashpoint upon which its relevance emerges is in the discussion of issues that are controversial within Catholicism. This paper, therefore, examines the question of ecclesial agency through an analysis of the pedagogical treatment of three controversial intra-Church topics and documents on the Church’s understanding of the laity. Its conclusion reveals several important considerations and questions that concern the foundational aims of Catholic schooling and what outcomes are assumed regarding the student’s current and future participation as a lay person in the Church.